A new species of the genus Opisthotropis Günther, 1872 (Squamata: Natricidae) from the highlands of Kon Tum Province, Vietnam - David, Patrick; Pham, Cuong The; Nguyen, Truong Quang; Ziegler, Thomas (Zootaxa, 2011)
A new species of the snake genus Opisthotropis Günther, 1872, Opisthotropis cucae sp. nov., is described from Kon Tum Plateau in central Vietnam. It is distinguished from any other Opisthotropis species by the combination of the following characters: (1) dorsal scales entirely smooth, in 23–19–19 rows; (2) 191 ventrals; (3) 1 loreal, in contact with internasal; (4) 7 supralabials, 5 th entering orbit; (4) dorsum uniformly greyish-brown without bands or crossbars, with an irregular separation between dark dorsum and venter, greyish-yellow speckled with dark grey. An extended comparison with other species of the genus Opisthotropis species is provided together with a key to the known species of the genus. Opisthotropis cucae sp. nov. is the third new mountain stream snake described from Vietnam in the past decade. The grammatical gender of the genus Opisthotropis is discussed; this genus is feminine.